Methods for Accessible Computer Science and Computer Programming Education for Visually Impaired and Blind Students - Güneş, Habibe (IGI Global, 2024)
Just like our fingerprints, we are born different from each other with many characteristics. What is expected from education is to respect these differences, to highlight individuals' unique and special characteristics, and to create experiences that will enable them to maximize their talents. However, when structuring education for individuals with special needs, it should be tailored to their individual needs and provide accessibility that allows them to develop skills relevant to the current technological age. In this book chapter, suggestions are presented for developing the basic skills of visually impaired individuals in computer science and coding education. © 2025 by IGI Global Scientific Publishing.
Keywords: Computer programming languages; Computer systems programming; 'current; Programming education; Special needs; Visually impaired; Students